2017
DOI: 10.1111/adb.12512
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D1 or D2 receptor‐expressing neurons in the central nervous system

Abstract: Dopamine signals mainly through D1 receptors (D1Rs) and D2 receptors (D2Rs); D1R-expressing or D2R-expressing neurons contribute to distinct reward and addictive behaviors. Traditionally, transgenic mice expressing green fluorescent protein (GFP) under D1R or D2R promoters are used for fluorescent verification in electrophysiology studies, whereas Cre mice are employed for behavioral research. However, it is unknown whether the same neuronal populations are targeted in GFP and Cre mice. Additionally, while D1R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
95
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(109 citation statements)
references
References 44 publications
10
95
3
1
Order By: Relevance
“…The direct visualization of D1R-and D2R-SPNs revealed that in the intermingled area, SPNs co-expressing both D1R and D2R were preferentially clustered adjacently to the corpus callosum. This contrasts with the homogenous distribution previously described in the anterior dorsal striatum (Gagnon et al 2017;Ren et al 2017;Wei et al 2018). The second territory, embedded between the striatum and the central amygdala is characterized by a high percentage of D1R/D2R-SPNs (~33%).…”
Section: Discussioncontrasting
confidence: 91%
“…The direct visualization of D1R-and D2R-SPNs revealed that in the intermingled area, SPNs co-expressing both D1R and D2R were preferentially clustered adjacently to the corpus callosum. This contrasts with the homogenous distribution previously described in the anterior dorsal striatum (Gagnon et al 2017;Ren et al 2017;Wei et al 2018). The second territory, embedded between the striatum and the central amygdala is characterized by a high percentage of D1R/D2R-SPNs (~33%).…”
Section: Discussioncontrasting
confidence: 91%
“…1). Striatal neurons mostly consist of GABAergic medium spiny neurons (MSN), which can be divided into two sub-populations as determined by the type of dopamine receptor they express: D1-or D2-expressing MSNs (Kreitzer & Malenka, 2008;Beaulieu & Gainetdinov, 2011;Gerfen & Surmeier, 2011;Calabresi et al, 2014;Wei et al, 2018). These neurons play opposite functional roles (Kreitzer & Malenka, 2008) in the socalled direct and indirect pathways, which were previously implicated in the action of drugs of abuse (Lobo & Nestler, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although the dopaminergic innervation of the hippocampus appears to be relatively limited (Hortnagl, Berger, Sperk, & Pifl, ; Scatton et al, ; Swanson and Hartman, ; Swanson, Kohler, & Bjorklund, ), hippocampus is significantly populated by dopamine receptors (Hansen and Manahan‐Vaughan, ; Smith and Greene, ; Wei et al, ) and the functional impact of DA in the hippocampus neural circuitry is substantial (Frey et al, ; Hansen and Manahan‐Vaughan, ; Ito and Schuman, ; Kempadoo, Mosharov, Choi, Sulzer, & Kandel, ; Lisman and Otmakhova, ; Takeuchi et al ; Werlen and Jones, ). Importantly, the DAergic projections from the ventral tegmental area and the substantia nigra are disproportionately segregated along the hippocampal long axis.…”
Section: Introductionmentioning
confidence: 99%